REAKSI SAHAM SEKTOR FARMASI DI BURSA EFEK INDONESIA TERHADAP VAKSINASI COVID-19 PERTAMA PRESIDEN JOKO WIDODO - Sukma Dwiyantika, Ni Kadek; Wirawan Yasa, Gerianta (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.08.TAHUN.2023DO - 10.24843/EEB.2023.v12.i08.p06, 2023)
This study aims to determine the reaction of pharmaceutical sector stocks to President Joko Widodo's first Covid-19 vaccination. The number of samples in this study were 18 companies, the sampling technique used non-probability sampling with saturated sampling method. The data analysis technique used is an event study with a hypothesis testing tool using the One Sample t-Test. The results of this study indicate that there are differences in abnormal returns before and after the administration of President Joko Widodo's first Covid-19 vaccination, where there was a positive reaction before the administration of the first Covid-19 vaccination to President Joko Widodo and a negative reaction at the time of administration on January 13, 2021 and after President Joko Widodo's first Covid-19 vaccination. This shows that it is important for investors to observe critically when absorbing and responding to signals, especially when making investment decisions.